Model of Interest in Buying Fashion Products on Tiktok Shop Which is Influenced by Influencer Marketing and Price Perception - Karina Dewi Pertiwi; Dini Andriyani; Adi Setiawan; Tiara Muthiarsih (CV. Media Digital Publikasi Indonesia, 2024)
In the rapidly developing digital era, competition between companies in the e-commerce sector is increasingly competitive. Social media is a supporting tool for consumers in sharing text, video, image and audio information, and currently technology is developing more quickly, because of the large number of internet users, therefore all activities can be done online, one of which is online shopping. one example is TikTok Shop. TikTok Shop is a social commerce feature that advertises and sells their products via TikTok. This shopping feature is present on TikTok as a response to increasing sales of various products after brands carried out promotions via social media platforms. Influencers are netizen actors who have social media accounts and continue to spread messages or campaign content to other netizens to strengthen the message or content. Influencer marketing is a marketing strategy in product sales by promoting a product by someone who is considered to have influence. Price is one component of a company's marketing strategy, with the aim of providing added value to consumers so that they continue to consume the products and services being sold. Consumers will tend to prefer a more affordable price to obtain an item. Consumers tend to prefer more affordable prices to get the goods they want. The aim of this research is to determine the formation of the Purchase Interest model which is influenced by Influencer Marketing and Price Perception. This research uses a side purposive method which involves selecting samples from the population studied based on certain criteria. Structural Equation Modeling (SEM) analysis was used to analyze the data. The results of the validity test output show that this research data is declared valid and the construct reliability test shows that each variable in this research is declared consistent. The statistical assumption test shows that it has a positive and significant effect on influencer marketing which can provide a stimulus to prices and purchasing interest which encourages customers to make purchases. The path analysis model fit test shows the similarity of several samples which can substitute for the population as a whole